Theoretical Investigation of All Optical Switching by Intersystem Crossing - Yuhao Zou; Haiwei Wang; Haozhe Huang; Zhihao Zeng; Kai Wang; Sicong Wang; Xiangping Li; Changsheng Xie (Applied Sciences, 2019)
The dynamics of spin flips induced by the femtosecond laser are theoretically investigated in this article. The spin flips in this scenario are attributed to the intersystem crossing (ISC) described within the frame of the Rabi model. This new explanation is a step attempting to explain the mechanism of the all-optical magnetic orientation switching in the perspective of the conservation of the angular momentum and breaks of the selection rule, which is ignored in the Raman scattering related explanations. The final spin states discussed herein are closely related to the intensity of the incident laser and the ISC decay rate. The quantitative analysis of the relation between decay rate, temperature and the intensity of the laser is discussed.